PENGARUH MOTIVASI, SELF EFFICACY DAN PERTIMBANGAN PASAR KERJA TERHADAP MINAT MAHASISWA JURUSAN AKUNTANSI UNTUK BERKARIR DI BIDANG PERPAJAKAN( STUDI KASUS PADA MAHASISWA UNIVERSITAS BHAYANGKARA JAKARTA RAYA ) - Hanifah, Saefani Nur; Khasanah, Uswatun; Yuniati, Triana (SINERGI : Jurnal Riset Ilmiah, 2025)
This research aims to analyze the influence of motivation, self-efficacy and labor market considerations on the interest of students majoring in accounting for a career in taxation (case study of students at Bhayangkara University, Greater Jakarta). This type of research is quantitative research, using a population of 236 accounting students who took part in the tax volunteer program and the technique used was probability sampling with a random sampling method based on the Slovin formula. The sample size was 70 after returning and sorting so that the data obtained was as large as 100 accounting student respondents who can be processed. The results of the research show that partially motivation, self-efficacy and job market considerations have a positive and significant influence on the interest of students majoring in accounting to pursue a career in taxation. Simultaneously, motivation, self-efficacy and job market considerations have a significant effect on accounting students' interest in pursuing a career in taxation